The complete mitochondrial genome of the redeye mullet Liza haematocheila (Teleostei, Mugilidae). (3rd September 2015) - Chen, Jianhua; Li, Yinglei; Chen, Haigang; Yan, Binlun; Meng, Xueping
Abstract: The complete mitochondrial sequence of the redeye mullet Liza haematocheila has been determined. The circle genome is 16, 822 bp in size, and consists of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and a control region. The gene order and composition of L. haematocheila was similar to that of most other teleosts. The base composition of H-strand is 26.42% (A), 26.38% (T), 16.72% (G) and 30.47% (C), with an AT content of 52.8%. All genes are encoded on the heavy strand with the exception of ND6 and eight tRNA genes. The mitochondrial genome of L. haematocheila presented will be in favor of resolving phylogenetic relationships within the family Scatophagidae and the Mugiliformes.